PENERAPAN LESSON STUDY BERBASIS SUPERVISI KELAS UNTUK MENINGKATKAN KEMAMPUAN MENGAJAR GURU PAI: (The Implementation of Lesson Study Based Class Supervision to Improve the Teaching Ability of PAI) - Zainuddin, Zainuddin (Uniqbu Journal of Social Sciences, 2022)
The aims of this study were to determine the effectiveness of the Lesson Study in improving the teaching ability of Islamic Religious Education (PAI) teachers in elementary schools in Mataram City's Cakranegara and Sandubaya sub-districts through Class Supervision. The problem formulation in this paper is based on the objectives stated above. Does the implementation of Lesson Study in Supervision class improve the teaching ability of PAI teachers in elementary schools throughout the Cakranegara and Sandubaya sub-districts of Mataram City? While the research method applied in this paper is qualitative. Where the researcher will describe the data in the form of sentences. Meanwhile, the researcher is conducting descriptive research. Whereas the descriptive approach describes only the phenomena, symptoms, events, and events that occur. The findings of this study show that; Classroom supervision using Lesson Study can improve the quality of learning by helping teachers to collaborate together to develop learning tools, and helps teachers to be innovative as an alternative that can encourage changes in learning practices in improving the quality of learning. This is due to the relationship between classroom supervision, the implementation of Lesson Study, and teachers' increasing ability in preparing learning tools and resources.